Social globalisation and efficiency of microfinance institutions nexus: empirical evidence on financial and social efficiency - Hussain, Hafezali Iqbal; Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina; Sufian, Fadzlan; Ali, Azlan; Saudi, Mohd Haizam (Kaunas University of Technology, 2022)
The main objective of this paper is to identify the impacts of social globalisation comprised of personal contacts, information flows and cultural proximity to the financial and social efficiency of Microfinance Institutions (MFIs). This study had conducted two stages of analysis, in which the first stage is Data Envelopment Analysis (DEA) approach and the second stage is multiple panel regression analysis under Generalized Least Square estimation method. The results exhibit that the overall MFIs operated in a relatively optimal scale during the period of the study. However, these MFIs were managerially inefficient in utilising their resources to achieve both social and financial efficiency. The results from panel regression analysis showed that only personal contacts exhibit a significant positive relationship with the financial efficiency of MFIs. This study could contribute new insights and implications to various parties, such as MFIs, policy makers, investors and researchers to improve the efficiency of MFIs.